Analysis of the Ornaments of the Pura Mangkunegaran Surakarta as Learning Material for Decorative Arts at SMPN 1 Mojogedang - Rita Anggraini; Zulfi Hendri (Journal of World Science, 2025)
Indonesia is rich in cultural heritage, yet many traditional arts and crafts, such as the ornaments of Pura Mangkunegaran Surakarta, remain underappreciated.  This research emphasizes integrating cultural heritage into decorative arts education to preserve cultural identity. Using a qualitative approach, the study identifies and analyzes various types, forms, and meanings of ornaments found in Pura Mangkunegaran Surakarta, their relevance, and the curriculum at SMPN 1 Mojogedang. The findings reveal that these ornaments, which reflect Javanese, Chinese, and European influences, not only enhance aesthetic appreciation but also foster critical thinking and creativity among students. By incorporating local cultural materials into educational practices, the research contributes to a deeper understanding of cultural backgrounds, instilling pride and a sense of responsibility in preserving heritage. This integration significantly enriches students' learning experiences and promotes cultural preservation within the educational framework.